Implementation of Digital-based Financial Inclusion for Millennials within the Society 5.0 Era: Implementation of Digital-based Financial Inclusion for Millenials Within the Society 5.0 Era - Faujiah, Nurul; Damayanty , Alfina (Tawazuna, 2022)
The ever-evolving era, followed by increasingly sophisticated technological advances, encourages people to innovate and continue to develop existing products. This article describes the use of digital-based financial inclusion for millennials in the era of "society 5.0." The author uses the library research method. After reviewing references from various sources, it was concluded that financial inclusion is a process in which economic actors, both individually and as a company, guarantee ease of access, availability, and the formal use of finance. The millennial generation dominates the number of internet users in Indonesia. One form of implementing digital-based financial inclusion used by millennials and often found in the era of "society 5.0" is digital payment technology launched by banks in the form of mobile banking